Penanaman Nilai Karakter Religius Pada Siswa Kelas X Di SMAN 1 Menganti Gresik - Abil Wafa Almaulana; Suhari Suhari (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
National character is an important pillar in the life of the nation and state. If the nation does not have national character, it will be difficult for the nation to become independent. One of the many characters that are applied is a religious character. The value of religious character is a value that is closely related to Belief in One Almighty God. Religious values in character education are very important because they become part of a person's belief in a true value that comes from the religion he believes in or adheres to and can be a strong motivation in building good character in a person both spiritually and naturally. The need for this character value is owned especially for students at SMAN 1 Menganti so that a person with good morals is formed.The purpose of this study was to examine the forms of instilling religious character values for class X students at SMAN 1 Menganti Gresik as a whole and also to identify the teacher's role in strengthening the inculcation of religious character values for class X students at SMAN 1 Menganti Gresik. This study used a descriptive qualitative method to find data on the inculcation of religious character values for class X students at SMAN 1 Menganti Gresik and the data was collected through observation, interviews, and documentation. The results of this study were obtained if the inculcation of the religious character values of students in class X at SMAN 1 Menganti had been carried out properly such as scheduling sunnah prayer activities, celebrating major religious events, getting used to behaving politely to everyon.